Performance of nonwoven geotextiles on soil drainage and filtration. Issue 5 (15th April 2020) - Sabiri, Nour-Eddine; Caylet, Adeline; Montillet, Agnès; Le Coq, Laurence; Durkheim, Yves
Abstract: The selection of a geotextile to prevent the soil suffusion in a civil engineering work is a classical problem. The internal erosion is a key factor as the migration of fine particles damages the integrity of the soil structure. This work deals with the problem of using a draining system consisting of a layer of soil and a geotextile sheet in order to prevent soil suffusion. It proposes a methodology which allows ordering the performance of nonwoven geotextiles. A range of experimental approaches were implemented including seepage flow tests under controlled flow rates. A detailed analysis of the data shows that intrinsic properties of geotextiles are not sufficient to predict their behaviour in a draining system. Moreover, the classical flow tests of the draining systems are not sufficient to adequately discriminate the three geotextile specimen used here. On the other hand, it seems important to use the history of the hydraulic gradient with respect to the flow rate variation. Thus, the present data of normalised relative pressure drop and normalised relative variation of flow rate are arranged in terms of a dimensionless criterion. This methodology enables evaluating and discriminating the performances of the geotextiles used here in terms of filtration and drainage functions.